2022
DOI: 10.1038/s41419-022-04632-z
|View full text |Cite
|
Sign up to set email alerts
|

Zeb1-induced metabolic reprogramming of glycolysis is essential for macrophage polarization in breast cancer

Abstract: Aerobic glycolysis (the Warburg effect) has been demonstrated to facilitate tumor progression by producing lactate, which has important roles as a proinflammatory and immunosuppressive mediator. However, how aerobic glycolysis is directly regulated is largely unknown. Here, we show that ectopic Zeb1 directly increases the transcriptional expression of HK2, PFKP, and PKM2, which are glycolytic rate-determining enzymes, thus promoting the Warburg effect and breast cancer proliferation, migration, and chemoresist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 68 publications
1
43
0
Order By: Relevance
“…An increase of glycolysis in tumors undergoing EMT will shape the TME into a lactate-rich environment, which will further perturb proper antitumor immunity. In line with this, Zeb1 induction in breast cancer has been demonstrated to be critical for pro-tumoral macrophage polarization [ 107 ]. This intrigues the question of whether the ablation of lactate signaling in TAMs will alleviate the aggressiveness of tumor.…”
Section: The Impact Of Tumor Aggressiveness On the Function Of Apcsmentioning
confidence: 87%
“…An increase of glycolysis in tumors undergoing EMT will shape the TME into a lactate-rich environment, which will further perturb proper antitumor immunity. In line with this, Zeb1 induction in breast cancer has been demonstrated to be critical for pro-tumoral macrophage polarization [ 107 ]. This intrigues the question of whether the ablation of lactate signaling in TAMs will alleviate the aggressiveness of tumor.…”
Section: The Impact Of Tumor Aggressiveness On the Function Of Apcsmentioning
confidence: 87%
“…Among the signaling intermediates identified above, the CREB pathway is known to link PGE2 signaling with macrophage polarization [ 52 ]. In fact, a CREB-C/EBPβ cascade has been shown to induce M2 macrophage-specific gene expression [ 53 ], and was higher in M2 polarized cells [ 54 ]. M2 polarization also correlates with a predominant arginase pathway and an increased production of polyamines, which can be responsible for tumor proliferation together with an anti-inflammatory response [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo and in vitro study showed that lactate induces VEGF expression and M2-like polarization of TAMs, both of which are mediated by HIF-1α [ 107 ]. Lactate targets the protein-coupled receptors on the surface of the TAMs membrane and induces M2-type polarization via the PKA/CREB pathway [ 174 ]. Additionally lactic acid produced under hypoxia is believed to be a weapon for activating pro-angiogenic TAMs and increasing PD-L1 protein expression in TAMs [ 172 , 175 , 176 ].…”
Section: Hypoxia-driven Crosstalk Between Tumor Cells and Tamsmentioning
confidence: 99%